Laboratory predictors of severe Coronavirus Disease 2019 and lung function in followed‐up. (5th May 2021) - Pan, Min; Wang, Rui‐rui; Chen, Xu; Han, Jun; Li, Qiang; Miao, Manli; Rao, Jianguo; Huang, Jizheng; Yu, Long; Xu, Yufei; Li, Lingli; Shao, Qiang; et al.
Abstract: Background: A pandemic caused by SARS‐CoV‐2 has infected more than 79 million people and killed exceeding 1.7 million people around the world by the end of 2020. Method: We obtained the clinical data of all diagnosed patients and lung function test of followed‐up patients in Fuyang, Anhui province to investigate laboratory predictors of severe Coronavirus Disease 2019 (COVID‐19) and the impairment of lung function. Results: Of the 155 patients, 87 (56.13%) were males. The mean age was 41.95 (SD 15.34) years. Only 30 (19.35%) patients had the critical condition. Fever (84.52%) was the most common symptoms, and short of breath was more common in severe patients ( p < 0.01). Lymphopenia was observed in most patients (74, 47.7%). It showed the elevation of CRP in 100 (64.5%) patients, the elevation of SAA or IL‐6 in 104 (67.1%) patients. The calculated cut‐off value of CRP was 19.35 mg/ml, the AUC was 0.777, sensitivity was 73.3%, specificity was 69.6%; SAA was 73.55 mg/L, 0.679, 83.3%, 56.8%, respectively; IL‐6 was 18.85 pg/ml, 0.797, 83.3%, 64.8%; D‐Dimer was 0.325 mg/L, 0.673, 66.7% and 68.8%. The combination of CRP, SAA, IL‐6, and D‐Dimer was 0.823 in AUC, 73.3% in sensitivity, and 78.4% in specificity. 12 (42.86%) followed‐up patients had completely normal lung function indicators. Conclusion: Elevated CRP, SAA, IL‐6 and D‐Dimer can be predictors to severe COVID‐19. The combination of these four indicators can improve the effectivity and specificity of assessing severe COVID‐19. Most of the followed‐up patients showed no abnormalities in lung function test. Abnormal lung function is mainly reflected in the diffusion function.